2008
DOI: 10.1182/blood-2007-09-112789
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of acute graft-versus-host disease by blocking T-cell entry to secondary lymphoid organs

Abstract: In acute graft-versus-host disease (aGVHD), donor T cells attack the recipient's gastrointestinal tract, liver, and skin. We hypothesized that blocking access to distinct lymphoid priming sites may alter the specific organ tropism and prevent aGVHD development. In support of this initial hypothesis, we found that different secondary lymphoid organs (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
109
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 50 publications
(90 reference statements)
12
109
0
1
Order By: Relevance
“…16,17 In contrast, other studies suggested that knockout of b7 was insufficient to modify intestinal GVHD, 18 and that blocking entry to specific secondary lymphoid organs (either peripheral lymph nodes or Peyer's patches) had no effect on GVHD, suggesting redundancy in secondary lymphoid tissue compartments. 19,20 Drawing general conclusions from these individual studies is difficult because of differences in the immunology of GVHD specific to the individual mouse models of HCT used in each of these separate studies. The evidence does support the theory that acute GVHD is initiated by allogeneic activation in secondary lymphoid tissue, with the induction of a specific trafficking phenotype dependent on the location of the secondary lymphoid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In contrast, other studies suggested that knockout of b7 was insufficient to modify intestinal GVHD, 18 and that blocking entry to specific secondary lymphoid organs (either peripheral lymph nodes or Peyer's patches) had no effect on GVHD, suggesting redundancy in secondary lymphoid tissue compartments. 19,20 Drawing general conclusions from these individual studies is difficult because of differences in the immunology of GVHD specific to the individual mouse models of HCT used in each of these separate studies. The evidence does support the theory that acute GVHD is initiated by allogeneic activation in secondary lymphoid tissue, with the induction of a specific trafficking phenotype dependent on the location of the secondary lymphoid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…6,13 Lack of CCR7 and CD62L expression on CTLs prevents migration to secondary lymphoid organs and further antigenic restimulations, although GVHD induction is only prevented if T-cell entry to all secondary lymphoid organs is impaired. 27 Expression of a 4 b 7 integrins, PSGL-1 and CXCR3 of CTLs, however, might facilitate entry into GVHD target organs but also into inflamed tissues, such as tumors. 28 Homing of CTLs into tumor sites was supported by the finding that the mastocytoma cell line P815 could be totally eradicated by CTLs, whereas the more aggressive B-ALL cells were only eradicated when injected with very low cell numbers.…”
Section: Discussionmentioning
confidence: 99%
“…60 (5) Geographic location: the interaction between the APCs and the donor T cells occurs primarily in the secondary lymph nodes, although in vivo imaging suggests that it also occurs in Peyer's patches. 61 However, although the secondary lymphoid organs are the likely location for the interaction of APCs and T cells, they are not obligatory for the development of GVHD. 62 Mediators of GVHD Donor T cells are the critical mediators of acute GVHD regardless of the type of antigen severity (Figure 2).…”
Section: Sensors Of Gvhdmentioning
confidence: 99%